Recent progress of endoplasmic reticulum stress in the mechanism of atherosclerosis - Ni, Lin; Yang, Luqun; Lin, Yuanyuan (Frontiers in Cardiovascular Medicine, 2024)
The research progress of endoplasmic reticulum (ER) stress in atherosclerosis (AS) is of great concern. The ER, a critical cellular organelle, plays a role in important biological processes including protein synthesis, folding, and modification. Various pathological factors may cause ER stress, and sustained or excessive ER stress triggers the unfolded protein response, ultimately resulting in apoptosis and disease. Recently, researchers have discovered the importance of ER stress in the onset and advancement of AS. ER stress contributes to the occurrence of AS through different pathways such as apoptosis, inflammatory response, oxidative stress, and autophagy. Therefore, this review focuses on the mechanisms of ER stress in the development of AS and related therapeutic targets, which will contribute to a deeper understanding of the disease's pathogenesis and provide novel strategies for preventing and treating AS.